Performance of JPEG Image Transmission Using Proposed Asymmetric Turbo Code. (28th December 2006) - Ramasamy Ramasamy, K. K.; Siddiqi Siddiqi, Mohammad Umar Mohammad Umar; Alias Alias, Mohamad Yusoff Mohamad Yusoff
Abstract : This paper gives the results of a simulation study on the performance of JPEG image transmission over AWGN and Rayleigh fading channels using typical and proposed asymmetric turbo codes for error control coding. The baseline JPEG algorithm is used to compress a QCIF (176 × 144 ) "Suzie" image. The recursive systematic convolutional (RSC) encoder with generator polynomials( 1, D 3 + D 2 + 1 / D 3 + D + 1 ), that is, (13/11) in decimal, and 3G interleaver are used for the typical WCDMA and CDMA2000 turbo codes. The proposed asymmetric turbo code uses generator polynomials( 1, D 3 + D 2 + 1 / D 3 + D + 1 ; D 3 + D 2 + 1 / D 3 + 1 ), that is, (13/11; 13/9) in decimal, and a code-matched interleaver. The effect of interleaver in the proposed asymmetric turbo code is studied using weight distribution and simulation. The simulation results and performance bound for proposed asymmetric turbo code for the frame lengthN = 400, code rater = 1 / 3 with Log-MAP decoder over AWGN channel are compared with the typical system. From the simulation results, it is observed that the image transmission using proposed asymmetric turbo code performs better than that with the typical system.